COVID-19 pandemic and adolescent mental health in China: Micro evidence and socioeconomic mechanisms - Chen, Boou; Zhao, Chunkai; Li, Xing; Liu, Jin (Frontiers in Psychology, 2022)
Although the impact of the COVID-19 pandemic on adolescent mental health has received sufficient attention in the medical and public health fields, analysis from the social science perspective is still lacking. By regarding the shock of COVID-19 pandemic as a quasi-natural experiment, this study adopts the Differences-in-Differences (DID) model and large microdata from Shandong Province, China, to identify the causal effect of the COVID-19 pandemic on the mental health of senior high school students. We find that the COVID-19 pandemic results in an increase of 2.5677 points in adolescent psychological problem scores, equivalent to an average decrease of 29.93% in mental health. Furthermore, results of mechanism tests show that this negative impact of the COVID-19 pandemic on adolescent mental health can be explained by a reduction in social trust, as well as widening inequalities caused by the digital divide and income gap. Moreover, the estimates suggest that the COVID-19 pandemic has a greater negative influence on the mental health of boys and urban adolescents. Our study complements the research field on the impact of the COVID-19 pandemic on adolescent mental health and the potential socioeconomic mechanisms from a new perspective. These findings provide insights into how to safeguard adolescent mental health in China and other countries in the pandemic prevention and post-pandemic era.